1985
DOI: 10.1017/s0043174500082011
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of14C-Glyphosate and14CO2-Labeled Photoassimilates in Canada Thistle (Cirsium arvense)

Abstract: Translocation of14CO2-labeled photoassimilates was compared to movement of14C-glyphosate [N-(phosphonomethyl)glycine] in Canada thistle [Cirsium arvense(L.) Scop. ♯ CIRAR] under field and controlled-environment conditions. Field-grown Canada thistle plants were treated on mature upper leaves at the midflower stage in mid-June and harvested 8 days later. No differences were found in glyphosate and assimilate distribution, and movement was primarily basipetal. Of the glyphosate and photoassimilates translocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 16 publications
1
29
0
2
Order By: Relevance
“…A few studies have indicated a correlation between herbicide and assimilate translocation (e.g. McAllister & Haderlie, 1985), with an increased nitrogen application increasing the quantity of assimilate and its translocation, thus resulting in an increased herbicide translocation. However, these mechanisms may differ between herbicides and weed species.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have indicated a correlation between herbicide and assimilate translocation (e.g. McAllister & Haderlie, 1985), with an increased nitrogen application increasing the quantity of assimilate and its translocation, thus resulting in an increased herbicide translocation. However, these mechanisms may differ between herbicides and weed species.…”
Section: Discussionmentioning
confidence: 99%
“…Applied glyphosate penetrates the plant tissue and is translocated, through the symplast or diffusely through the apoplast, to the root and shoot meristems . The transport of this herbicide is associated with the assimilate pathway, and glyphosate accumulates mainly in the youngest, most active plant parts, where it affects the target enzyme . Although the target enzyme is present in all plant tissues, it is expressed most in meristem tissues.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to xenobiotic molecules such as herbicides, little is known about their loading into the phloem. However, it is generally assumed that xenobiotic transport in the phloem follows the direction of sucrose flow (118,119). Hence, in species where sucrose molecules are loaded through the apoplastic pathway, it is conceivable that xenobiotic molecules may be loaded similarly.…”
Section: Modeling Phloem Translocation Of Xenobioticsmentioning
confidence: 99%